Rejecting resettlement: the case of the Palestinians - Irfan, A (Refugee Studies Centre, University of Oxford, 2017)
Palestinian rejection of resettlement was driven by political concerns. This case study shows the importance of engaging directly with refugees when devising durable solutions.